Mastitis in the dairy herd at Taman Pertanian Universiti Putra Malaysia - Khan, Lee Ching; Ramanoon, Siti Zubaidah; Bejo, Siti Khairani (2011)
This study investigated mastitis in the dairy herd at Taman Pertanian Universiti Putra Malaysia (TPU). Questionnaire was used to describe the farm performance and management. Nineteen lactating cows and 150 quarters were tested by clinical examination, the California Mastitis Test (CMT) and bacteriological culture to estimate the incidence and prevalence of mastitis. Relationship between subclinical mastitis and some risk factors were evaluated. Prevalence of the aetiologic agents and their antibiotic sensitivities were also determined. Some management deficiencies were identified. No clinical mastitis observed. The incidence risk of subclinical mastitis based on CMT was 8 cases in 100 cows and 6 cases in 100 quarters, in a 2-week period. The period prevalence of subclinical mastitis by CMT was 68% (cows) and 48% (quarters), and from culture, 100% cows and 91% quarters. Staphylococcus hyicus (68%) was predominant followed by Staphylococcus aureus (32%). Prevalence of subclinical mastitis by CMT or culture was significantly associated with positive CMT, position of quarters, and stage of lactation. Antibiotics sensitivity and resistance of the isolates were identified. In conclusion, the prevalence of mastitis in the dairy herd at TPU was high. Hence, the results of this study would be useful for the prevention and control programme for mastitis in this herd.